Bioconversão do exoesqueleto do camarão para elaboração de filme biodegradavél a base de quitosana - Melo, Michelle Rayssa Pereira de (2014)
The Brazilian production of marine shrimp is mainly focused on the domestic market, which better absorbs the headless and peeled product, which generates significant amount of agro-industrial waste. The objective of this research was to develop biodegradable films of chitosan from the exoskeleton of marine shrimp vannamei Litopeanaeus added liquid smoke for use in sausages. For characterization of chitosan obtained from the exoskeleton of shrimp were employed methodologies for determining viscosity , conductometry , spectroscopy in the infrared and x-ray diffraction to characterize the polymer and performed tests of tensile strength , elastic modulus , solubility , opacity and thickness to characterize the films . The results were efficient for the determination of chitosan, and consistent with the literature regarding the characterization of polymeric films of origin. Microbiological analyzes were performed on the sausages before and after preparation according to ANVISA Resolution on January 12, 2001, in the chitosan films with and without plasticizer added to liquid smoke for coating sausages in order to increase the shelf life of the product the antimicrobial activity of the films was determined by the agar diffusion method on bacterial strains: Escherichia coli active, Pseudomonas aeruginosa and Staphylococcus coagulase positive. In the results , not presence of coliforms at 45 º C , coagulase Staphyilococcus positive , were observed Clostridium sulfite reducer was not detected the presence of Salmonella sp, as the antimicrobial activity , inhibition zones were found in biofilm added liquid smoke , only to Escherichia coli. As for the sensory properties of sausages packaged in three types of biodegradable chitosan film extracted from the exoskeleton of marine shrimp were differentiated by the addition of liquid smoke concentrations: 5 %, 7% and 10%. A nine-point hedonic scale was used to analyze the difference of control and acceptance testing were assessed using internal preference mapping (MEDPRF). The results indicated a significant difference between the control, conventional polyethylene film and biodegradable chitosan film plus smoke. By Preference Mapping revealed that the coated film containing sausages with liquid smoke in concentrations of 5 % and 7 %, no statistical differences obtained for the attributes: Appearance, Aroma, Taste, texture and overall acceptance levels in the addition of adding smoke compared to the control sample and 10 % ¨ smoke. It was observed in this work that the mechanical analyzes of biodegradable chitosan film is presented as a low elasticity and high tensile strength , and acceptable as opacity, solubility and thickness and that more research needs to be conducted in order to prepare chitosan films more flexible and resistant.